The Camp Fire Girls : Gender, Race, and American Girlhood, 1910-1980 - Helgren, Jennifer, 1972- (Book collections on Project MUSE., 2022)
"Through the lens of America's first and most popular girls' organization, Jennifer Helgren traces the role and changing meaning of American girls' citizenship across critical intersections of gender, race, class, and disability in twentieth-century America"--